The effects of cooperative learning model on attitudes towards physical education and self-efficacy - Serhat Turan; Tugba Zehir; Ozgecan Ilgin; Fikret Soyer (Ozlem Book Center, 2023)
This study was carried out because the effect of cooperative learning on attitudes and self-efficacy towards physical education and sports was not discussed in the literature and the effects of the model could not be fully elucidated. A total of 48 students, 24 male and 24 female, studying in the 7th grade of secondary school participated in the study. The study was carried out according to the pretest-posttest control group experimental design. Lessons were given to 24 students in the experimental group on the jigsaw technique of the cooperative learning model for 8 weeks. In the control group, the direct instruction model is used. In the study, in order to determine the attitude and self-efficacy towards physical education, the "Scale of Aptitude to Physical Education" is applied to the students before and after the 8-week education. In the study, data are obtained with "Independent t test" and "paired sample t test". While there is no important difference between the groups at the beginning of the study, important differences are found in the attitude and self-efficacy scores in favor of the experimental group as a result of the trainings. As a result of the study findings, with the jigsaw technique, students' commitment to physical education increases and their beliefs about their skills are strengthened. The study reveals important results as it fills a gap in terms of literature and illuminates the effects of the cooperative learning model from different angles.